INFLUÊNCIA DOS CICLOS LUNARES NA PRODUÇÃO DE HORTALIÇAS - Stein, Rose B. A.; Schneider, Everton R.; Pirocca, Laura; Schröder, Tatiana; Rustick, Fernando E.; Perin, Débora (Salão do Conhecimento, 2013)
Resumo